ANALISIS PERBANDINGAN PENDAPATAN USAHATANI KENTANG SEBELUM DAN PADA MASA PANDEMI COVID-19 DI KECAMATAN KERTASARI, KABUPATEN BANDUNG - Widia Kintan Sabila Firdaus; Eliana Wulandari; Dini Rochdiani; Zumi Saidah (Universitas Galuh Ciamis, 2021)
Potato is an annual vegetable crop that can replace staple food. The increase of potatoes needs lead to the majority of farmers in Kertasari to grow potatoes as one of their agricultural commodities. The Covid-19 pandemic had an impact on the agricultural sector, such as a decrease in the selling price of agricultural products which also occurred in potato. This study aimed to analyze the income of potato farming before and during the Covid-19 pandemic in Kertasari. This study uses a quantitative research design using a questionnaire as a research instrument. The research was conducted in Cibeureum and Cikembang Villages in Kertasari to 44 potato farmers from August to November 2020. Data analysis in this study used income analysis, R/C analysis, and paired sample t-test. The result showed that there was a significant difference between the income of potato farming before the Covid-19 pandemic and during the Covid-19 pandemic, and had a value of R/C above 1 indicating that potato farming in Kertasari is profitable and feasible to be performed.